The Failure of Soviet Economic Planning : System, Performance, Reform - Campbell, Robert W. (Robert Wellington), 1926-2015 (Book collections on Project MUSE., 1992)
Although the Soviet Union's centrally planned economic system played a significant role in world economic growth and modernization, it ultimately failed to compete with market forms of economic organization. Despite unavailing efforts at reform, it has now been abandoned, as the republics of the former USSR move painfully toward the market. Robert W. Campbell, one of the most respected U.S. specialists on the economy of the former Soviet Union, probes the evolution, behavior, and fatal weaknesses of the Soviet administrative-command economy. His essays cover a broad set of perspectives--theoretical interpretation of the Soviet-type economy and the growth model that went with it, concrete analyses of individual sections and functions, evaluation of the microeconomics of Soviet decision making, and descriptions of attempts at institutional and doctrinal reforms. They provide instructive background on some of the biggest problems now facing the Commonwealth of Independent States, such as the monetary and fiscal collapse engendered by reform, the looming fuel and energy disaster, and the seemingly intractable task of transforming the military-industrial complex and integrating its resources into the civilian economy. Robert W. Campbell's outstanding work provides an indispensable resource for understanding what the Soviet economic system was and the problems it faced in the transition to the market model.